The Mediating Role of Resilience in The Relationship Between Game Addiction and Sleep Disorders in College Students - Taş, İbrahim; Bilgin, Okan; Eker, Halime (Faculty of Philosophy, University of Novi Sad, 2025)
Gaming addiction has attracted the attention of researchers and clinicians as a current and growing problem. Increased gaming addiction can lead to problems such as sleep disorders. The present study aimed to examine the mediating effect of resilience on the relationship between game addiction and sleep disorders in college students. The study was conducted on 320 college students aged between 20 and 27 years. The Internet Gaming Disorder Scale, Brief Resilience Scale, and DSM-5 Sleep Disorders Scale were used as data collection tools. In the analysis of the data, the SPSS package program and the PROCESS macro were used. The results revealed that gaming addiction significantly predicted resilience in a negative direction and sleep disorders in a positive direction. Resilience, in turn, significantly predicted sleep disorders in a negative direction, and it mediated the relationship between gaming addiction and sleep disorders. The findings demonstrated that resilience emerged as a significant process variable linking gaming addiction and sleep-related outcomes, suggesting that lower resilience may partially account for the pathway through which gaming behaviors affect sleep quality.
Keywords: Game Addiction; Sleep Disorders; Resilience; Mediating Variable